Enhancing Citizenship Education Through The Use of Secondary School Textbooks of English in The Algerian Context a Case Study : Year Two Textbook - Semahi, Meriem; Gasmi, Mustapha (Faculty of Letters and Foreign Languages Department of English, 2024)
This research tries to investigate the feasibility and effectiveness of incorporating civic education in English language textbooks in Algerian secondary schools. Consistent with the country's emphasis on enhancing civic values and duties, mixed-method research is used. The present study, therefore, aims to contribute to educational policy and practice. For this, the content in second-year English textbook and survey of English language teachers were analysed. Through an examination of the present textbook, teachers' views toward this new type of content, and how citizenship-focused language education resources effect on students in Algeria; from the perception of the researchers, this research will contribute significantly to understanding how language education resources can be used for promoting citizenship education in Algeria. The study is aimed to provide programs designers and policy makers with a plan of action to strengthen the integration of citizenship education into English language curriculum so as to be capable of preparing competent, productive and civic pride citizens in Algeria English. Conclusively, the current second-year textbook of English used in Algerian high schools shows a praiseworthy effort to realize citizenship education but there are still major areas that need to be refined.